Assessing Risk Priority Numbers of Failures in the Screw Tightening Machine of a Hard Disk Drive Production System - Naraphorn Paoprasert; Wai Yan Htet Lin; Thepniramit Muneekaew (Journal of Machine Engineering)
In a competitive environment, many production industries must reduce costs while maintaining asset value and reliability. In the manufacturing process, the machine is essential because downtime can inhibit and stop production. This study investigated the breakdown trend of a hard disk drive production line in the manufacturing industry to recommend applying Reliability-Centered Maintenance (RCM) for improved productivity, reliability, and availability. This study focused on breakdown analysis, identifying potential failures, and classifying the main components of screw-tightening machines. The RCM method was used based on several tools: failure mode and effects analysis (FMEA), risk priority number (RPN), mean time between failures (MTBF), and mean time to repair (MTTR). The study identified which production line had the lowest availability and productivity due to high downtime and failure rates. In addition, the top-five failures were identified that severely disrupted production These breakdowns were overcome and their occurrence reduced was by calculating and evaluating MTBF and MTTR to help manage failures and indicate the efficiency of corrective action. Thus, this industry and others can achieve better equipment availability and machine reliability using the RCM method.